The study of the book Ta’limul Muta’allim in shaping the character of students at Madrasah Diniyah Showlatiyah Balikpapan - Fatimah, Siti; Sintianingrum, Nadila; Blouin, Aberald (At- Ta'lim : Jurnal Pendidikan, 2025)
This research aims to find out how learning the book Ta'limul Muta'allim influences the character formation of students at Madrasah Diniyah Showlatiyah Balikpapan. This research uses a qualitative approach. The subjects of this research were the Head of Madrasah Diniyah Showlatiyah Balikpapan, the teacher of the book Ta'limul Muta'allim, the teaching staff of Madrasah Diniyah Showlatiyah Balikpapan and several students who studied the book Ta'limul Muta'allim, namely classes V and VI of Madrasah Diniyah Showlatiyah Balikpapan. The data collection methods used were observation, interviews and documentation. The collected data is analyzed by processing data from sources, then explaining the data and drawing conclusions from the research results. The results of the research show that (1) the learning of the book Ta'limul Muta'allim at Madrasah Diniyah Showlatiyah Balikpapan in this learning begins with reading the study prayer, interpreting the book led by the ustadz using the bandongan method, asking several students to read the book that has been interpreted, then Ustadz reviews previous material before going into new material, explains material using the lecture method, Ustadz makes natural reflections so that learning doesn't feel bored, strengthens students' understanding by asking questions when there is material they don't understand, provides historical stories related to material that requires it, closes learning with closing prayers and greetings. (2) the character instilled in learning the book Ta'limul Muta'allim at Madrasah Diniyah Showlatiyah Balikpapan. Namely religious character, curiosity character, environmental care character, patient character, compassion character, honest character, disciplined character, waro character.